Reassessing Fano Resonance for Broadband, High‐Efficiency, and Ultrafast Terahertz Wave Switching. Issue 2 (17th November 2022) - Hu, Yuze; Tong, Mingyu; Hu, Siyang; He, Weibao; Cheng, Xiang'ai; Jiang, Tian
Abstract: Miniaturized ultrafast switchable optical components with high efficiency and broadband response are in high demand to the development of optical imaging, sensing, and high‐speed communication. Sharp Fano‐type resonance switched by active materials is one of the key concepts that underpins the control of light in metaoptics with high sensitivity. However, actuating such metasurfaces exhibits a long‐standing trade‐off between modulation depth and operational bandwidth. Here, the limitations are circumvented by theoretical analysis, numerical simulation, and experimental realization of an achromatic Fano metasurface so that a high contrast of tunability with ultrafast switching rate over a broad range of frequency is achieved. By developing the physics of inter‐mode coupling, the Fano metasurface is designed according to a complete phase diagram derived from coupled mode theory. Unlike conventional Fano metasurfaces, the cross‐polarized inter‐metaatoms coupling is discovered as a superior ability of high‐efficiency broadband achromatic polarization conversion. To prove the ultrasensitive nature, a metadevice is constructed by incorporating a thin amorphous Ge layer with a weak photoconductivity perturbation. Transmission modulation over broadband frequency range from 0.6 to 1.1 THz is thus successfully realized, featuring its merits of modulation depth over 90% and On–Off–On switching cycle less than 10 ps. Abstract : Fano‐type metamaterials switched by active materials enable the control of light in metaoptics with high sensitivity. However, they exhibit a long‐standing trade‐off between modulation depth and operational bandwidth. Here, the authors circumvent this limitation by proposing a novel Fano‐type metasurface with high contrast of tunability and broadband ultrafast switching, which is extremely appealing for next‐generation flat photonic devices.